KAJIAN EPIDEMIOLOGI KEJADIAN LEPTOSPIROSIS DI KOTA SEMARANG DAN KABUPATEN DEMAK TAHUN 2008 - Bambang Yuniarto; Tri Ramadhani (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2010)
Leptospirosis is one of rodent borne neglected diseases, but health problem in day. Transmision of Leptospirosis occurs by contact with water or humid soil contaminated with urine from rodent infected with Leptospira. The aim of this research was to know epidemiology Leptospirosis in Semarang City and Demak District, in April-November 2008. The design of this research was cross sectional. The activity included Leptospirosis diagnosis with Rapid Diagostic Test (Leptotek Dri Dot) and rat trappings. Data were analysed descriptively by using tables, graphics and maps. The result showed that in 2008, Leptospirosis incidence in the both areas was higher compared to the previous year. The Leptospirosis cases tended to increase in the rainy season. In Semarang City, Leptospirosis cases were mostly found in the age group of 0-19 years (44,1%) and 51% of the total cases were female. In Demak District, the cases were mostly found in the age group of 40-49 years (25,7%) and 75,7% from the total cases were male. The spesies rats found in this research were Rattus tanezumi, R.norvegicus, B.indica, Mus musculus, R.exculan and Suncus murinus. Kidney test of the rats caught in Semarang City showed Rattus tanezumi, R.norwegicus, B.indica, and R.exculan were infected with Leptospira sp.